2021
DOI: 10.1002/ctm2.519
|View full text |Cite
|
Sign up to set email alerts
|

CircIMMP2L promotes esophageal squamous cell carcinoma malignant progression via CtBP1 nuclear retention dependent epigenetic modification

Abstract: Background Esophageal squamous cell carcinoma (ESCC) is one of the most aggressive cancers. The two major lethal causes of ESCC are diagnosis at an advanced stage and lymph node metastasis (LNM). Circular RNAs (circRNAs) play critical regulatory roles in cancer progression, though, largely through unclear mechanisms. However, the character of circRNAs in the malignant progression of ESCC remains unclear. Methods The circRNA microarray was used to explore the circRNAs that were differentially expressed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Liu Z focused on the role of circDOPEY2 and concluded that circDOPEY2 inhibited CPEB4-mediated Mcl-1 translation process and enhanced chemosensitivity of ESCC 48 . Liang Y reported that CircIMMP2L promoted ESCC progression via CtBP1 nuclear retention dependent epigenetic modification 49 . We discovered a novel circRNA named hsa_circ_0003823 by identifying the circRNA and mRNA expression profiles of 3 pairs of ESCC tumor and paracancerous tissues, which was also the most up-regulated circRNA in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Liu Z focused on the role of circDOPEY2 and concluded that circDOPEY2 inhibited CPEB4-mediated Mcl-1 translation process and enhanced chemosensitivity of ESCC 48 . Liang Y reported that CircIMMP2L promoted ESCC progression via CtBP1 nuclear retention dependent epigenetic modification 49 . We discovered a novel circRNA named hsa_circ_0003823 by identifying the circRNA and mRNA expression profiles of 3 pairs of ESCC tumor and paracancerous tissues, which was also the most up-regulated circRNA in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that circRNAs are involved in epigenetic regulation, including histone and chromatin modifications. circIMMP2L mediates the malignancy of esophageal squamous cell carcinoma (ESCC) by promoting the nuclear retention of CtBP1 [ 44 ]. In the nucleus, circIMMP2L mediates the interaction between CtBP1 and HDAC1 and induces the deacetylation of histone H3 in the promoter regions of E-cadherin and p21 .…”
Section: Biological Roles Of Circrnasmentioning
confidence: 99%
“…circIMMP2L (hsa_circ_0081964) is derived from exons 2–4 of the Inner Mitochondrial Membrane Peptidase Subunit 2 ( IMMP2L ) gene. circIMMP2L has significantly higher expression in ESCC tissues from patients with an advanced TNM stage and lymph node metastasis [ 44 ]. The expression of plasma circIMMP2L in patients with advanced-stage ESCC or lymph node metastasis was significantly upregulated compared to that in healthy individuals.…”
Section: Function Of Circrnas In Esophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported the role of circRNA in almost every activity of life mediated by protein sponging. CircPOK increased the IL6 transcript by combining with ILF2/3 to occupy the promoter of IL6 [ 16 ]; The circIMMP2L regulated epigenetic remolding in esophageal squamous cell carcinoma by inducing CtBP1 nucleus retention [ 17 ]; The circACC1 up-regulated the glycolysis and β-oxidation by ensuring the stability of AMP-activated protein kinase (AMPK) protein [ 18 ]; The circVAMP3 negatively regulated hepatocellular carcinoma (HCC) mediated by cell cycle-associated protein 1 (CAPRIN1) and Stress Granule Assembly Factor 1 (G3BP1) interaction-dependent phase separation [ 19 ]. Some nuclear-localized circRNAs played roles in the splicing and transcription of its cognate endogenous transcript [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%